Netizens’ Perspective towards Electronic Money and Its Essence in the Virtual Economy: An Empirical Analysis with Special Reference to Delhi-NCR, India - Mohammed Arshad Khan (Complexity)
This research attempts to evaluate the ongoing position of the modalities exercised in India concerning digital payments. Largely appraised as a success story in the making, this research examines several instrumental factors in India’s digital payment systems. It further extends to identifying the impact of demographic attributes and constructive variables, such as service quality, reliability, satisfaction, and security on digital payment system, Delhi NCR, India. A Google form questionnaire was adopted to collect data through online mode. The researcher collected the primary data from 165 respondents. Purposive sampling method was exercised, along with CFA technique and parameter test used through SPSS (version 25), reliability issue, validity issue, and model fitness achieve through SPSS-AMOS (version 24). The significant peculiarities and analysis are presented further in this research contributing to a precise depiction of findings and then, based on it, the conclusion.